MENERAPKAN PENTINGNYA NILAI-NILAI KEJUJURAN DI DALAM BERBISNIS: STUDI ANALISIS Q.S AL-MUTHAFFIFIN 1-3 BERDASARKAN TAFSIR AL-MISBAH - Hariki, Wahyudi Zulfa; Isty, Muhammad Athurjaza; Farhan, Nabil; Hermanto, Edi (IAINU Kebumen Prodi IAT, 2025)
In the business world, honesty is a basic value that is very important to build good relationships between businesss people and consumers. This study aims to explore the understanding of honesty in business in the Qur'an, especially Q.S. Al-Muthaffifin verses 1-3, as well as its implications in modern business practices. This research uses a qualitative approach with a library research method, analyzing primary sources such as the Qur'an and M. Quraish Shihab's Al-Mishbah commentary. As well as secondary sources that involve collecting and analyzing data from literature and reliable sources related to business ethics and honesty. The findings show that honesty in business not only includes truth in statements and actions, but also involves transparency and integrity in every business interaction. The research also highlights that honesty can increase trust between businesses and customers, and contribute to business sustainability. In addition, this research found that the fraudulent practices described in Q.S. Al-Muthaffifin verses 1-3 can damage a company's reputation and social relationships, and carry severe moral consequences in the afterlife. Therefore, the application of honesty values is necessary to create a good and sustainable business environment.